Diseño e implementación de un sistema de aero generación de flujo turbulento para la obtención de energía eléctrica para una vivienda en el sector de Pasachi, El Morro, cantón Latacunga, provincia de Cotopaxi, periodo académico 2014-2015 - Duchi Lopez, Victor Alfonso (2015)
The research topic concerns the design and implementation of a wind turbine, where the specifications and materials analysis operation of the elements that constitute the machine for power generation was demonstrated. The prototype build on good wind conditions being able to generate 144 kWh to have a generation voltage of 18V DC 8A with an amperage that is sufficient to cover the demand housing 209 Jan w. For this, the system will consist of a mechanical, electrical and electronics that make the process of converting the kinetic energy of wind into alternative energy and subsequently become capable of supplying continuous power to the battery charging and turn it into useful energy for housing. The contribution of this project is aimed at the principles of good living encouraged by the national government fulfilling the objective 3, which is to improve the quality of life of the population to thereby lead a fulfilling and dignified life.